Mechanical rotary coupling with one-sided locking capability - L.FEVRE; DUPONT ELODIE (2025)
The subject of the invention is a mechanical coupling device for selectively rotationally coupling a first shaft with a second shaft. The coupling device comprises the following components: a first rotating mechanism which is determined to be fixedly connected with the first shaft in a rotating manner; -a first rotational mechanism, which is intended for rotationally fixed connection to the first shaft,-a second rotational mechanism, which is intended for rotationally fixed connection to the second shaft,-a rotationally fixed ring, which surrounds the first mechanism and the second mechanism along an overlapping section where the first mechanism and the second mechanism overlap; -a locking unit for the rotation of the first shaft through the second shaft, the locking unit comprising a groove defined by a ring and an elastic element and a rolling body enclosed in the groove; wherein the rolling body is held in a position clamped in the recess in such a way that the rolling body is pressed by an elastic element